Studies on the flora of the North Blosseville Kyst and on the hot springs of Greenland.
The vascular plants and bryophytes found by recent expeditions to the north Blosseville Kyst, East Greenland, are recorded. Four species, all occurring by the hot springs in Knighton Fjord (69°22’ N. !at., 24°43’ W. long.), are new to the flora of Greenland: Archidium alternifolium (HEDW.